1976
DOI: 10.1007/bf00453607
|View full text |Cite
|
Sign up to set email alerts
|

Lokale pO2- und pH2-Messungen mit Nadelelektroden zum Studium der Sauerstoffversorgung und Mikrozirkulation des Innenohres

Abstract: The local partial pressure of oxygen (pO2) and the rate of hydrogen elimination were measured in the three scalae of the basal turn of 28 Guinea-pig cochleae under conditions of normoxia, hyperoxia and hypercapnia and with acoustical stimulation with the needle electrodes developed by Baumgärtl and Lübbers. In the scala tympani a pO2 decrease from the round window toward Corti's organ was registered and pO2 values of over 100 mm Hg were measured near the membrane of the round window and of 10-40 mm Hg near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Since cochlear hypoxia occurs before evidence of reduced CoBF at exposure to 101-, 106-and 115-dB SPL broad-band noise, we suppose that cochlear oxygen deficiency measured during acoustic overstimulation with pure tones [11-13, 15, 18-20], broad-band noise [14,15,18,20], impulse noise [16] or gun shots [17] did not result from reduction in CoBF, as has been suggested so far. An important question asked here is why noise results in cochlear hypoxia and whether this induces hearing loss or is merely an epiphenomenon occuring at the same time as the hearing loss.…”
mentioning
confidence: 89%
“…Since cochlear hypoxia occurs before evidence of reduced CoBF at exposure to 101-, 106-and 115-dB SPL broad-band noise, we suppose that cochlear oxygen deficiency measured during acoustic overstimulation with pure tones [11-13, 15, 18-20], broad-band noise [14,15,18,20], impulse noise [16] or gun shots [17] did not result from reduction in CoBF, as has been suggested so far. An important question asked here is why noise results in cochlear hypoxia and whether this induces hearing loss or is merely an epiphenomenon occuring at the same time as the hearing loss.…”
mentioning
confidence: 89%
“…Several indirect ways of measuring CBF were used during the 60s and 70s with the aim of measuring metabolism and the influence of drugs and adrenergic control [9][10][11][12][13][14].…”
Section: Cochlear Microcirculation In Laboratory Animals and Manmentioning
confidence: 99%
“…Maass et al [12] measured the peri lymphatic oxygen tension by penetrating the round window membrane with an oxygen sensing microelectrode. They found that the perilymphatic oxygen tension was higher near the round window membrane and lower in the deeper parts of the tympanic peri lymph.…”
Section: Commentsmentioning
confidence: 99%
“…Furthermore, oxygen was found to pass from the middle ear to the inner ear through the round window membrane [12][13][14].…”
Section: Introductionmentioning
confidence: 99%